SPECIFICITIES OF FRUIT FREEZE DRYING AND PRODUCT PRICES - Ivančević, Savo; Mitrović, Dragan; Brkić, Miladin (Economics of Agriculture, 2012)
Freeze drying, as relatively new process of drying in vacuum at very low temperatures, ensures the preservation of all thermo labile compounds in the initial raw material, and final low content of moisture provides microbiological stability and permanent preservation of products. Red raspberry, because of relatively high content of water (90%), specific structure of aggregate fruit, characteristic bright colour and flavour, was not preserved up to now by conventional drying. This paper gives an overview on the two different methods of drying fruits: freeze drying and convective drying. Raspberry sorts Willamette and Meeker were dried by freeze drying, as well as by conventional drying with warm air of low relative humidity. Freeze drying was performed in the device Christ Alpha I/5 under desublimers temperature of -55°C and processing temperature of raw material of -35°C. Fruits of the sort Willamette were dried to a fnal moisture content of 18.86%, and Meeker up to 16.15%. Also, some changes in chemical composition, overall aroma, sensory characteristics, density and volume, water activity, loss of vitamin C, the degree of rehydration of the dried fruit in comparison to fresh one were tested. Gained results show that freeze drying can effectively preserve the chemical composition, volume, colour and aroma of raspberry. In the paper of authors from foreign countries the influence of different technologies for the products preservation was tested as freezing, freeze drying (or lyophilisation) and conventional drying. Tests were done with the main goal to determine the qualitative changes on strawberry, raspberry, gooseberry, elder, apricot, sour cherry, apple and cornelian cherry. All preservation technologies have reduced the amount of biologically active compounds, such as vitamin C and phenolic compounds. Related to the chemical composition of fresh fruit, decrease of tested parameters was affected by freezing for 15%, freeze drying for 28-32% and conventional drying for 45-48%. The process of freeze drying is among one of the methods for preservation of raw materials of plant origin (fruits, vegetables, spices and herbs). Final product has a high nutritional value (as fresh fruits and vegetables). Freeze dried products do require special storage conditions (e.g. absence of light, packaging materials with low gas permeability, inert atmosphere, etc.). In this way dried products represent the basis for instant soups, bakery, dairy and confectionery products.